Procalcitonin Levels in The Patients of Multiple Sclerosis - Akbulut, Handan; Bulut, Serpil; Kansız, Fatma (Fırat University, 2003)
Aim: Bacterial infections may cause relapse of multiple sclerosis (MS) that is a demyelinating infection of Central Nervous System. PCT is a protein that raises some clear bacterial infections. In the present study, we aimed to determine PCT levels at MS patients. Material and method: A total of 39 Relapsing-Remitting MS (RR-MS) patients (aged 17-51 years) who refered to Firat Medical Center Multiple Sclerosis out-patient's clinic were included in this study. Thirteen (33%) of the patients were in attack period and 26 (%66.7) were in remission. The control group was formed 39 healthy volunteer subjects. The PCT levels were studied by immunoluminometric assay method (ILMA). Results: The procalcitonin levels were 0.39±0.05 ng/mL in MS patients and 0.17±0.06 ng/mL in controls. The PCT levels were 0.25±0.05 ng/mL and 0.31±0.09 ng/mL in attack and remission period, respectively (p>0.05). Conclusion: The PCT levels were determined any elevation neither at remission nor at attack.

Amaç: Santral sinir sisteminin demiyelinizan hastalıklarından olan multiple skleroz (MS)'da, bakteriyel infeksiyonların hastalığın alevlenmesine neden olabileceği belirtilmektedir. Prokalsitonin (PCT) belirgin bakteriyel infeksiyonlarda yükselen bir proteindir. Bu çalışmada MS hastalarında prokalsitonin değerlerinin saptanması amaçlanmıştır. Gereç ve yöntem: Fırat Tıp Merkezi Multiple Skleroz Polikliniği'nde takip edilen, 17-51 yaşları arası 39 Relapsing-Remitting MS (RR-MS) hastası çalışma kapsamına alındı. Hastaların 13'ü (%33,3) atak dönemindeydi ve 26'sı (%66,7) remisyonda idi. Kontrol grubunu 39 sağlıklı gönüllü oluşturdu. PCT immünoluminometrik assay (İLMA) metodu ile çalışıldı. Bulgular: MS hastalarında prokalsitonin değerleri 0.29±0.05 ng/mL olarak gözlenirken, kontrol grubunda 0.17±0.06 ng/mL olarak tespit edildi (p>0.05). Atak dönemindeki MS grubunda prokalsitonin düzeyi 0.25±0.05 ng/mL, remisyon döneminde ise 0.31± 0.09 ng/mL olarak tespit edildi (p>0.05) . Sonuç: Sonuç olarak MS hastalarında gerek remisyon gerekse atak döneminde anlamlı prokalsitonin yüksekliği tespit edilmemiştir.
Multiple Skleroz Hastalarında Prokalsitonin Düzeyleri